Synthesis and Pharmacological Evaluation of Piperidine Derivatives with Various Heterocyclic Rings at the 4-Position - TAKAI, HARUKI; SHUTO, KATSUICHI; HASHIMOTO, TAMOTSU; TERANISHI, MASAYUKI; KUBO, KAZUHIRO; OBASE, HIROYUKI; NAKAMIZO, NOBUHIRO (Chemical & pharmaceutical bulletin, 1985)
A series of piperidine derivatives with various heterocyclic rings at the 4-position was prepared and tested for antihypertensive activity and other biological activities. The antihypertensive effects of the present compounds in the spontaneous hypertensive rat were less potent than those of previously reported compounds. However, among the compounds tested for antiulcer activity and antiinflammatory activity, some exhibited interesting properties.